(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The advancement of scientific and technological knowledge is reshaping the legal relationship between humans and animals, posing unprecedented challenges for the law and fostering more advanced protection paradigms. This study examines the existing gap between scientific evidence and EU legislation, identifying three distinct legislative approaches – adaptive (e.g., the Netherlands), moderate (e.g., Germany), and rigid (e.g., Italy) – based on the degree of integration of scientific findings into national legal frameworks. The analysis demonstrates that a more flexible and dynamic legal model is essential to ensuring timely and effective animal protection, particularly considering the forthcoming revision of the EU Animal Welfare legislation, (re)scheduled for 2026.